Optimizing Energy Efficiency in Vertical Axis Wind Turbines: A CFD Analysis of Inlet Velocity and Fluid Type Impact - Haris Nubli; Seung Jun Baek; Nabella Sofa Nur Afiqoh; Yuki Trisnoaji; Singgih Dwi Prasetyo (Universitas Sebelas Maret, 2025)
The development of Vertical Axis Wind Turbines (VAWTs) has become a key focus in renewable energy utilization due to their ability to operate at low wind speeds and their simple design. This study aims to analyze the effects of inlet velocity variations and fluid physical properties on flow patterns, turbulence, and kinetic energy in VAWTs. The simulation was conducted using the Computational Fluid Dynamics (CFD) method, based on ANSYS Fluent, for a 2D turbine model with a diameter of 12 cm. Inlet velocity variations of 10, 11, 12, 13, and 14 m/s were tested using three types of fluids: air, helium, and hydrogen. The results show that increasing inlet velocity transforms the flow pattern from stable to complex, with greater turbulence forming behind the cylinder. Air exhibited the highest kinetic energy at low to medium velocities, ranging from 10 to 12 m/s, which was up to 24.7% higher than that of helium and 3.8% higher than that of hydrogen. At higher velocities, 13–14 m/s, the kinetic energy difference among the three fluids decreased to less than 1.5%. Furthermore, outlet velocity was consistently higher than inlet velocity for all fluids, with hydrogen achieving the highest acceleration at 14 m/s.